Managing ideas for the development of new products. (1st January 2002) - Nilsson, Lars; Elg, Mattias; Bergman, Bo
It is ideas that act as initiators of new product development projects. In the literature, ideas for the development of new products are found to originate from different sources both external and internal to an organisation. For example, formalised product development processes use customer surveys and technology development in order to find ideas for new products while integration with a lot of other idea sources is less evident. Some organisations have identified this weakness and created arenas where ideas can be discussed and exchanged between individuals. One example of an arena is idea management systems, which are formal ways of capturing, examining, nurturing, storing and developing ideas created in an organisation. In this paper, the role of idea management systems in three multinational Swedish organisations is studied. The findings suggest that idea management systems can be used to introduce and strengthen the innovation capability of an organisation.